Gulls as carriers of antimicrobial resistance genes in different biogeographical areas of South America - Lorenti, Eliana Andrea (2021)
The aim of this communication was to establish if Enterobacterales associated with gulls in Argentina harbored antimicrobial resistance (AMR) genes. We analyzed cloacal swabs in two contrasting areas: Ensenada, Buenos Aires province (26 Larus dominicanus and 22 Chroicocephalus maculipennis) and Puerto Madryn, Chubut province (20 L. dominicanus). In Ensenada, blaCTX-M and mcr-1 genes, were isolated from both gull species, whereas in the Puerto Madryn, only blaCTX-M gene was found. We report for the first time C. maculipennis as carrier of AMR. The finding of AMR in wildlife constitutes a useful tool in evaluating the anthropogenic impact on environmental health.